PENGARUH KOMPETENSI, PENGEMBANGAN KARIR DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN (Studi Pada Balai Penelitian Tanaman Pemanis dan Serat Jawa Timur) - Yuyuk Liana (Politeknik Negeri Malang, 2018)
A conducive company will grow and develop by focusing on its human resources in the hope of optimally carrying out the function of its human resources. The objectives in this study are: (1) To examine the simultaneous effect between competence, employee career development and work motivation on employee performance? (2) To examine the simultaneous effect between competence, employee career development and work motivation on employee performance? The population in this study were civil servants in the Environment Research Center for Sweetener Crops and East Java Fiber as many as 171 employees. While the sample used in the study was 77 people. The results of the study show that there is a significant and simultaneous influence between competencies, career development and work motivation on employee performance. Furthermore, which has the greatest influence is the competence variable that is equal to 0.484.